The clinician's handbook of natural medicine - Pizzorno, Joseph E.; Murray, Michael T.; Joiner-Bey, Herb (Churchill Livingstone, 2015)
Get instant, easy access to the natural medicine expertise you need with The Clinician's Handbook of Natural Medicine, 3rd Edition. Written by leading authorities in complementary and integrative medicine, this portable handbook offers clear and rational directives on diagnosing and treating 80 diseases and disorders with natural medicine. Inside the pages you'll find concise summaries of diagnostic procedures, general considerations, therapeutic considerations, and therapeutic approaches for each condition, as well as naturopathic treatment methods like dietary changes, physical therapy advice, exercise modifications, and recommended supplements and botanical medicines. Based on Pizzorno's trusted Textbook of Natural Medicine, 4th Edition and the most current evidence available, it's your key to accessing reliable, natural diagnosis and treatment options in any setting